2013
DOI: 10.1016/j.labeco.2013.02.002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of receiving supplementary UI benefits on unemployment duration

Abstract: We consider the consequences of working part-time on supplementary unemployment insurance benefits in the Danish labour market. Following the "timing-of-events" approach we estimate causal effects of subsidized part-time work on the hazard rate out of unemployment insurance benefit receipt. We find evidence of a negative lock-in effect and a positive post-treatment effect, both of which vary across individuals. The resulting net effect on the expected unemployment duration is positive for some groups (e.g. mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 19 publications
2
31
1
4
Order By: Relevance
“…To do so we follow the approach developed by Kyyrä et al (2009) and calculate the expected remaining unemployment duration of entering a temp job at a given unemployment duration and at a given treatment duration, compared to the counterfactual of no treatment, i.e the average treatment effect on the treated. The median time until entry into the first temp job is about 11 weeks in our sample, and the median duration of a temp spell during an unemployment spell approximately 6 weeks.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…To do so we follow the approach developed by Kyyrä et al (2009) and calculate the expected remaining unemployment duration of entering a temp job at a given unemployment duration and at a given treatment duration, compared to the counterfactual of no treatment, i.e the average treatment effect on the treated. The median time until entry into the first temp job is about 11 weeks in our sample, and the median duration of a temp spell during an unemployment spell approximately 6 weeks.…”
mentioning
confidence: 99%
“…Despite these tremendous expenses, studies 27 have generally shown that the effects of most activation programs are modest and sometimes even negative (e.g., Card et al 2009). In Denmark, activation policies that involve some real working experience for unemployed workers, in particular employment subsidies in private firms, seem to be most effective (see, e.g., Kyyrä et al 2009, Rosholm & Svarer 2008, Jespersen et al 2008. Almost all other program types show remarkably large lock-in effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, a Danish study finds significant lock-in effects in part-time unemployment [11]. The Danish system of unemployment benefits is more generous than the other systems studied.…”
Section: Empirical Evidencementioning
confidence: 69%
“…Thus, it might be advisable to direct these benefits to workers with weaker connections to the labor market. The results of the Danish study suggest that youth and immigrant workers reap the largest gains from part-time unemployment insurance [11].…”
Section: Competing Interestsmentioning
confidence: 96%